Contemporary Challenges of India’s Foreign Policy - Pandey, Stuti (Journal of Ecohumanism, 2025)
From a vantage point, Indian foreign policy is drastically different from its initial predilections. This paper briefly traces the development of India’s foreign policy and zooms in on the contemporary challenges and opportunities for foreign policy of India by briefly analysing its relations with the neighbouring countries such as China, Pakistan, Nepal, Bangladesh, Sri Lanka, Bhutan, and Myanmar, with the western countries, namely the United States, the United Kingdom, Canada and Europe, and Russia and West Asia. India of the 21st century needs to navigate these complexities of global dynamics to position itself as a Viswaguru or world leader.